SISTEM FONOLOGI BAHASA KODI DI PULAU SUMBA - Ni Putu Ekayani; Aron Meko Mbete; A.A. Putu Putra (Program Magister Linguistik Universitas Udayana, 2014)
This study focus on a language in Sumba Island, the language of Kodi (BK). Two issues that underlie this study, namely (1) how the inventory of phonemes in BK of Sumba Island, and (2) how the distinctivefeaturesof languagephonemeinventory of BK? Analyzeis done in the form of 350 BK lexicons, which captured through unstructured interviews to five informants who are native speakers of BK. By the generative phonology theory, this qualitative study are summarized in two findings. First, that BK has five vowel phonemes /i, e, a,o, u/, with allophones in the two, namely the phoneme/e/with allophones [e] and [?] as well asthe phoneme/o/with allophones [o] and [?]. BK has 20 consonant phonemes: /p, t, c, k, ?, ?, ?, ?, m, n, ?, mb, nd, nj, ng, l, h, r,w, y /. Sylabel pattern of BK is consist of minimum V (vocal) dan maximum CV (consonant+vocal), because this is a open vocalic language. Second, it can be concluded that based on the basis of distinctive features, phonemeson BK was divided into five groups (feature ofthe main categories, place of articulation, manner of articulation, traits stem tongue, and extra features) and totaled 18 distinguishing features.